Gender Differences in the Perceptions of Genuine and Simulated Laughter and Amused Facial Expressions. (January 2015) - McKeown, Gary; Sneddon, Ian; Curran, William
This article addresses gender differences in laughter and smiling from an evolutionary perspective. Laughter and smiling can be responses to successful display behavior or signals of affiliation amongst conversational partners—differing social and evolutionary agendas mean there are different motivations when interpreting these signals. Two experiments assess perceptions of genuine and simulated male and female laughter and amusement social signals. Results show male simulation can always be distinguished. Female simulation is more complicated as males seem to distinguish cues of simulation yet judge simulated signals to be genuine. Females judge other female's genuine signals to have higher levels of simulation. Results highlight the importance of laughter and smiling in human interactions, use of dynamic stimuli, and using multiple methodologies to assess perception.